Ocean Observing and the Blue Economy - Rayner, Ralph; Jolly, Claire; Gouldman, Carl (Frontiers in Marine Science, 2019)
Sustained ocean observations provide an essential input to ocean scientific research. They also support a wide range of societal and economic benefits related to safety, operational efficiency and regulation of activities around, on, in and under our seas and ocean. The blue or ocean economy is large and diverse, accounting for around US$1.5 trillion of global gross value-added economic activity. This is projected to more than double by 2030. Sustainably delivering this growth in economic activity is fundamentally dependent on ocean observations. This review paper summarizes the projected changes in the scale and scope of the ocean economy and the role that observations, measurements and forecasts play in supporting the safe and effective use of the ocean and ocean resources, at the same time as protecting the environment. It also provides an overview of key future work being planned to develop a better understanding of the present and likely future ocean economy and the role and value of ocean observations in its sustainable realization.